Oblubieniec widziany oczami oblubienicy w Pieśni nad Pieśniami - Drawnel, Henryk (The Biblical Annals, 2017)
The Canticle seen in its literal, non-alegorical or spiritual, sense recounts the story of a profound love relationship between an anonymous man and an anonymous woman. Their mutual love is expressed by the two fundamental terms dôdîm and ’ahăbāh that are mainly used by the bride, hence the feminist approach to the text. These two terms on the lips of the bride do not refer exclusively to the erotic aspect of love, but, to the contrary, implicate an involvement of the whole person of both the bride and bridegroom. The concept of love rises quite often from the sensual description of the body to the transforming experience of love the purpose of which is to create a full and exclusive communion with the beloved. Thus the experience of love in the Canticle utterances formulated by the bride should be inscribed within the context of the creation account (Gen 2) that stresses the communion between man and woman. Love in the Canticle should also be analyzed in the context of aesthetic categories characteristic to poetic compositions that tend to positively transform the object of love by using the language of metaphor and symbol.